ON THE EVOLUTION OF GEOGRAPHICAL THOUGHT AND THE SYSTEMATIZATION AND REPRESENTATION OF GEOGRAPHICAL INFORMATION - Cesar de Souza, Paulo (Revista Gênero e Interdisciplinaridade, 2025)
This text is the result of the selection process test for the Master's degree in the Postgraduate Course in Geography at FCT/UNESP, Presidente Prudente, in 2002. The systematization and representation of geographic information comprises a set of theoretical and methodological knowledge that provides an understanding of the evolution of geographic information, mainly from the end of the Middle Ages to the present day. The importance of geographic information for the human sciences, as well as for other areas, leads society to identify how this information was processed in the way it is today, imbued with a lot of technique, diversity of knowledge, objects of study and objectives, such as the technological development of scientific and informational means and their technologies, as well as their formalization for social, economic, political and environmental use. Along with them, we can note the evolution of geographic knowledge itself and its contribution to the formation of a more humanized society that enables the inclusion of individuals/citizens in the globalized world and in the inhabited space.